An outbreak of a novel recombinant Coxsackievirus A4 in a kindergarten, Shandong province, China, 2021. Issue 1 (31st December 2022) - Li, Juan; Ni, Nan; Cui, Yanan; Zong, Shuai; Yao, Xue; Hu, Tao; Cao, Mengyuan; Zhang, Yong; Hou, Peiqiang; Carr, Michael J.; Xing, Weijia; Zhou, Hong; et al.
ABSTRACT: In 2021, twenty children exhibiting influenza-like illnesses were reported from a kindergarten in Shandong Province, China. Eleven genomes of Coxsackievirus A4 (CV-A4) were obtained from the pediatric cases, sharing <93% genome sequence identities with known CV-A4 strains. Further analyses suggested potential genetic recombination in the P3 region of the novel strains.